تقييم قدرة بحيرة السن على المعالجة الذاتية من التلوث بالفوسفور (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Self-cleansing of lake for phosphorus (P) pollution identifies sum of mechanisms manage the phosphorus sink to sediments from solution: P co-precipitation with calcium carbonate or P precipitation; This study illustrated that the value of calcite saturation index was(SIcalcite= 3.6) and the ratio was (SIcalcite/HAP= 0.31) which were both positive. Besides,Sediments had 62% oftotal phosphorus as apatite inorganic phosphorus (181.4mmoL.L-1). These parameters were not sufficient for lake to be recovered, due to high content of organic P and bioavailable P in terms of high value of Carlson's index (TSI = 80.1) which indicates typical trophic status. All indicators lead to fact that P is transported into Al-Sinn aquifer from Non-point resources of pollution in Al-Sinn Basin. Therefore, strategies are highly recommended to control the buildup of trophic status. يقصد بالمعالجة الذاتية للبحيرة من التلوث بالفوسفور مجموعَ الميكانيكيات التي تؤدي إلى تنظيم إخراج الفوسفور من الوسط المائي باتجاه الرواسب: ترسيبُ الفوسفور مع كربونات الكالسيوم؛ لقد بينت الدراسة أن قيمة دليل التشبع بالكالسيت(SIcalcite= 3.6) ونسبته إلى دليل تشبع بالهايدروكسيأباتيت (SI calcite/SIHAP = 0.31)، وهما قيمتان إيجابيتان،  كما احتل تركيز الفوسفور بشكله الأباتيتي نسبة (62%) من الفوسفور الكلي المتواجد في الرواسب (181.4mmoL.L-1). لكن لا تعتبر هذه القيم كافية لتعافي البحيرة في ظل ارتفاع نسبة الشكل المتاح للنشاط الحيوي ونسبة الجزء العضوي منه، وهذا يبينه قيمة دليل كارلسون المرتفعة (TSI = 80) التي تدل على فرط تغذية نموذجي. تقود كل هذه المؤشرات إلى أن الفوسفور ينتقل بشكل رئيسي إلى الحامل المائي المغذي للنبع من المصادر غير المحددة المنتشرة على امتداد حوض السن، وليس المحيطة به بشكل مباشر. هذا ما يستدعي وضع استراتيجيات لاحتواء الحالة قبل تفاقمها.